Comportamento de um motor de ciclo diesel com diferentes configurações de injeção e misturas de biodiesel - Sala, José Antonio (2020)
Diesel cycle engines are widely used to carry out the most diverse agricultural activities in Brazil. They are used from single cylinder engines, with low power demand to large engines that exceed 500 hp. The use of biodiesel in a blend with petroleum diesel is a reality and in the last 15 years there has been a gradual increase in the concentration of renewable fuel. Currently, the mandatory percentage is 10% with regulations already allowing the addition of up to 30%. In January 2017, the first Brazilian regulation for pollutant emissions in agricultural and road machinery, MAR-I, came into force. To meet the requirements of this regulation, it was necessary to migrate the mechanical fuel injection system to the electronic fuel injection system. The work seeks to analyze the behavior of the engine in the face of changing injection parameters and the variation in the content of biodiesel in mixture. The tests were carried out at NEMA - UFSM on an agricultural tractor with a four cylinder engine, supercharged and with electronic fuel injection. The electronic system works with sensors and actuators and, in this way, the electronic remapping was done, changing the reading of the pressure sensors so that a greater amount of fuel was injected and of the crankshaft's angular position, so that an advance of the injection point occurred in 2,5º. Tests were carried out with Diesel B10 sold in the fuel stations network and also mixtures of 20% and 30% biodiesel, all with 10 ppm of sulfur. The tests were performed under full engine load from 1300 to 2000 rpm. In addition to torque, power and consumption, CO, HC, NO, NO2 and MP emissions were also evaluated. The advance of the injection point caused an increase in power and a decrease in specific fuel consumption in all fuels, but increased levels of emissions, mainly of MP for the B20 and B30. The greater amount of injected fuel provided an average power gain of up to 14.96% and an average torque of 15.50%. The emissions limit of MAR-I was only exceeded in two tests. With B30 fuel and advance of the injection point and increased amount of injected fuel exceeded the MP limit and with B20 fuel and increased amount of injected fuel exceeded the NOx + HC limit. In view of the results, reprogramming of the electronic injection system is necessary when biodiesel is added to the fuel mixture.